2006
DOI: 10.1590/s0036-46652006000300004
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology and occupational and environmental variables for leptospirosis, brucellosis and toxoplasmosis in slaughterhouse workers in the Paraná State, Brazil

Abstract: SUMMARYLeptospirosis, brucellosis and toxoplasmosis are widely-distributed zoonosis, being the man an accidental participant of their epidemiological chains. The aim of this paper was to make a seroepidemiological report and identify occupational and environmental variables related to these illnesses in 150 workers in a slaughterhouse in the Northern region of Paraná. For the diagnosis of leptospirosis a microscopical seroagglutination test was applied; for brucellosis, the tamponated acidified antigen test an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
17

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 7 publications
3
29
0
17
Order By: Relevance
“…A quarterly serological monitoring in seronegative pregnant women can ensures the diagnosis and provide the early treatment of this infection (1) . The results of this study added to others (12,13) indicated that control measures to toxoplasmosis in humans from this small municipality in Paraná must focus on sanitary education for all population, whether urban or rural areas.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…A quarterly serological monitoring in seronegative pregnant women can ensures the diagnosis and provide the early treatment of this infection (1) . The results of this study added to others (12,13) indicated that control measures to toxoplasmosis in humans from this small municipality in Paraná must focus on sanitary education for all population, whether urban or rural areas.…”
Section: Resultsmentioning
confidence: 51%
“…The very similar serologic results detected between rural and urban populations from this study possibly occurred due to their similar cultural and food customs. Other studies on pregnant women (12) and slaughterhouse workers (13) in this city showed the seroprevalence to toxoplasmosis had been affected by educational level, but not among those residences in rural or urban areas. The overall seroprevalence detected (70.00%) suggests a large distribution of infection.…”
Section: Resultsmentioning
confidence: 69%
“…La prevalencia en población general también varía dependiendo del área geográfica que se estudie, pudiendo estar en alrededor de 1,2 a 6% en estudios recientes en poblaciones de América del Sur 2,3 . Por otro lado, se han realizado estudios de prevalencia los últimos 20 años, en grupos de población [4][5][6][7] , grupos de alto riesgo [8][9][10][11][12][13][14][15] y contactos de enfermos 16 , encontrándose resultados variables dependiendo de la zona y la ocupación, pero donde los factores de riesgo se repiten: exposición a aguas contaminadas, manipulación de animales, contacto con animales, regiones con inundaciones frecuentes y áreas pobres y rurales. Sin embargo, se estima que su magnitud está subestimada debido a su amplio espectro clínico y a la falta de métodos diagnósticos que sean sensibles y específicos 17 .…”
Section: Introductionunclassified
“…En Brasil la evaluación de diferentes patógenos en trabajadores de matadero, mostró una prevalencia del 4,0% para Leptospira spp., sin embargo, el análisis de riesgos evidenció que solo los casos de Leptospira spp. se debían a una infección ocupacional mostrando la relevancia de esta enfermedad [25].…”
Section: Discussionunclassified